Occupational back pain among schoolteachers in Jordan: estimated prevalence and factors associated with self-reported pain and work limitations. Issue 3 (3rd July 2018) - Alghwiri, Alia; Marchetti, Gregory
Abstract : Purpose . To investigate the point prevalence of upper back pain and lower back pain in Jordanian schoolteachers and to estimate the work-related reported disability. Method . A cross-sectional survey was used to assess back pain in a convenience sample of teachers in Jordan. Crude and weighted prevalence estimates of self-reported spinal pain and limited productivity were described. Demographic and occupational factors associated with self-reported pain and limited productivity were identified by multinomial/logistic regression. Results . Crude rates differed by gender, geographic location, school funding and grade levels of teaching. Weighted estimates for self-reported pain were 46% for females and 36% for males. Pain with limitation was 55% for males and 49% for females. Pain without limitation was associated with female gender (odds ratio [ OR ] = 5.26). Pain with limitations was associated with female gender ( OR = 2.92), teaching in public school ( OR = 2.06) and body mass index ( OR = 1.1). Among subjects with pain, limitations were associated with male gender ( OR = 2.34), teaching in public school ( OR = 3.18) and pain in both upper and lower back ( OR = 4.64). Conclusions . Pain and occupational limitations are highly prevalent in schoolteachers in Jordan.